Low-Complexity Distributed Multibase Transmission and Scheduling. (30th April 2008) - Skjevling Skjevling, Hilde Hilde; Gesbert Gesbert, David David; Hjørungnes Hjørungnes, Are Are
Abstract : This paper addresses the problem of base station coordination and cooperation in wireless networks with multiple base stations. We present a distributed approach to downlink multibase beamforming, which allows for the multiplexing ofM user terminals, randomly located in a network withN base stations. In particular, we detail a low-complexity scheduling algorithm, which can be employed with different objective functions, exemplified here by two approaches: (1) maximizing the sum rate of the network; and (2) maximizing the number of users served, given a statistical constraint on the received rate per user. The optimizations are based on locally available information at each base station. Results show that our approaches yield significant gains, when compared to schemes that do not allow cooperation between cells. These gains are obtained without the extensive signaling overhead required in previously known multicell MIMO processing.